2019
DOI: 10.1080/20909977.2019.1617547
|View full text |Cite
|
Sign up to set email alerts
|

Characterisations of the Late Cenomanian reservoirs in Asala Field, East Bahariya concession, Northern-Western Desert, Egypt

Abstract: The study aimed to combine the different available data to understand the subsurface system and the characteristic of reservoirs in Asala Field to represent the vertical and lateral heterogeneity at the well, multi-well and field scale, which could be used as a tool for reservoir management. Seismic interpretation was conducted on the seismic sections that concerned the study area to make a detailed structural interpretation to determine the structural geometry of the horizons. Petro-physical well log analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The sediments recorded by deep drilling in the northern Western Desert have shown that this large area is differentiated beneath its flat cover of younger sediments into a number of major paleo geographic basins. These sedimentary basins were the scope of numerous investigations by many geologists such as [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. [23] and [24].…”
Section: Stratigraphic Settingmentioning
confidence: 99%
“…The sediments recorded by deep drilling in the northern Western Desert have shown that this large area is differentiated beneath its flat cover of younger sediments into a number of major paleo geographic basins. These sedimentary basins were the scope of numerous investigations by many geologists such as [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. [23] and [24].…”
Section: Stratigraphic Settingmentioning
confidence: 99%